Pengaruh Literasi Keuangan dan Pengetahuan Investasi terhadap Keputusan Investasi Mahasiswa Fakultas Ekonomi dan Bisnis Universitas Negeri Padang melalui Minat Investasi sebagai Variabel Intervening - Rahma Yani; Efni Cerya (Wawasan : Jurnal Ilmu Manajemen, Ekonomi dan Kewirausahaan, 2024)
This study aims to determine the effect of financial literacy and investment knowledge on investment decisions of students of the Faculty of Economics and Business, Universitas Negeri Padang through investment interest as an intervening variable. The population in this study were students of the Faculty of Economics and Business, Universitas Negeri Padang. This study uses Purposive Sampling technique, and the determination of the number of samples using the Cochran formula, which is 97 samples. The data used is primary data. The analysis method used is path analysis with the help of SPSS 26. The results showed that: 1) Financial literacy has a significant effect on investment decisions, 2) Investment knowledge has a significant effect on investment decisions, 3) Investment interest has a significant effect on investment decisions, 4) Financial literacy has a significant effect on investment interest, 5) Investment knowledge has a significant effect on investment interest, 6) Financial literacy has a significant effect on investment decisions through investment interest as an intervening variable, and 7) Investment knowledge has a significant effect on investment decisions through investment interest as an intervening variable.